2015
DOI: 10.1093/mnras/stu2665
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the active galactic nuclei population with extreme X-ray-to-optical flux ratios (fx/fo > 50)

Abstract: The cosmic history of the growth of supermassive black holes in galactic centers parallels that of star-formation in the Universe. However, an important fraction of this growth occurs inconspicuously in obscured objects, where ultraviolet/optical/near-infrared emission is heavily obscured by dust. Since the X-ray flux is less attenuated, a high X-ray-to-optical flux ratio ( f x / f o ) is expected to be an efficient tool to find out these obscured accreting sources. We explore here via optical spectroscopy, X-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…Many of these objects have X-ray-to-optical flux ratios above 1, and a small fraction of about 5% have F X /F opt ≥ 20 (Della Ceca et al 2015). J103621.39-581520.0 thus seems to be a particularly X-ray active quasar.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these objects have X-ray-to-optical flux ratios above 1, and a small fraction of about 5% have F X /F opt ≥ 20 (Della Ceca et al 2015). J103621.39-581520.0 thus seems to be a particularly X-ray active quasar.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g. Fiore et al 2003;Mignoli et al 2004;Alexander et al 2002;Del Moro et al 2009;Della Ceca et al 2015) have found that sources with high f x / f O are characterised, on average, by red optical to near-infrared colours (R − K Vega > 5) and column densities in the X-ray of the order of 10 21−23 cm −2 . Moreover, VLT X-Shooter Perna et al 2015) and SINFONI observations of a small subsample of obscured QSOs at z ∼ 1.5, selected on the basis of their observed red colours and high f x / f O ratio, have confirmed the presence of ionised outflowing material in 75% of objects and a dust-reddened type 1 nature.…”
Section: Introductionmentioning
confidence: 99%
“…Among seven EXO50s studied in Della Ceca et al (2015), three are classified as EDOGs (f24/fR > 2000). Their absorption column densities NH are measured to be > 0.4, 3.61 +1.03 −0.92 , and > 0.1 × 10 22 cm −2 .…”
Section: Mid-infrared Emission and Obscuration Of Agnmentioning
confidence: 99%
“…Optically faint sources also tend to be bright in mid-infrared relative to the optical bands if detected in the mid-infrared band. 24 µm to R-band flux ratios (F24/FR) of some sources exceed 1000 (Lanzuisi et al 2009, Brusa et al 2010, Della Ceca et al 2015, which is a criterion of dust-obscured galaxies (Dey et al 2008). Among 43 objects with F24/FR > 2000 in the sample of Lanzuisi et al (2009), at least 23 are X-ray bright optically faint for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation